2019
DOI: 10.2174/1874944501912010439
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Triage Amongst Nurses Working in the Emergency Departments of Rural Hospitals in Limpopo Province

Abstract: Background: Many deaths in hospitals occur within 24 hours of admission. Some of these deaths could be prevented if the patients were effectively triaged, identified quickly, and treatment initiated without delay. Triage and emergency care have always been weak and under-emphasized components of healthcare systems in rural areas of Limpopo Province, and yet, if well organised, it could lead to saving many lives and reducing the ultimate costs of care. There have been few studies, and there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 16 publications
2
20
3
Order By: Relevance
“…Various authors have investigated and deliberated on the level of knowledge and skills of nurses working in the ED regarding triage in South Africa [ 6 , 7 , 8 , 9 , 10 , 11 ]. For instance, Phukubye, Mbombi, and Mothiba [ 6 ] reported nurses in the Sekhukhune District of Limpopo Province in South Africa (SA) had an average score on knowledge of triage with poor practical skills. Similarly, a study by Dulandas and Brysiewicz [ 7 ] reported a need for a support system in educational development that will improve the competency, knowledge, and practical skill level among most emergency nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have investigated and deliberated on the level of knowledge and skills of nurses working in the ED regarding triage in South Africa [ 6 , 7 , 8 , 9 , 10 , 11 ]. For instance, Phukubye, Mbombi, and Mothiba [ 6 ] reported nurses in the Sekhukhune District of Limpopo Province in South Africa (SA) had an average score on knowledge of triage with poor practical skills. Similarly, a study by Dulandas and Brysiewicz [ 7 ] reported a need for a support system in educational development that will improve the competency, knowledge, and practical skill level among most emergency nurses.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the development of items according to the views of the participants has increased the reliability of the results of determining triage nurses' professional capability. This is another strength of the present study [32].…”
Section: Discussionmentioning
confidence: 59%
“…Inadequate to moderate triage knowledge among EMS personnel is not restricted to this study. It has been documented by numerous studies across several countries (Sarikaya et al , 2004; Sedaghat et al , 2012; Mirhaghi and Roudbari, 2017; Kerie et al , 2018; Duko et al , 2019; Chen et al , 2003; Rahmati et al , 2013; Phukubye et al , 2019; Fry and Burr, 2001; Göransson et al , 2005; Asgari et al , 2018; Sherafat et al , 2019).…”
Section: Discussionmentioning
confidence: 90%
“…It is essential for all personnel responding to an MCI incident to share the triage fundamentals and knowledge to achieve effective coordination, communication and task sharing, which will be reflected in the accuracy of triage decisions (Frykberg, 2005). The previous studies have reported that nurses do not have sufficient knowledge about triage; the reported levels ranged from poor to moderate levels of knowledge among emergency healthcare providers (Sarikaya et al , 2004; Sapp et al , 2010; Sedaghat et al , 2012; Mirhaghi and Roudbari, 2017; Kerie et al , 2018; Duko et al , 2019; Chen et al , 2003; Rahmati et al , 2013; Phukubye et al , 2019; Fry and Burr, 2001; Göransson et al , 2005). A descriptive survey was used to examine the perception of Saudi Arabia EMS students concerning their preparedness for disaster management.…”
Section: Introductionmentioning
confidence: 99%